Spatial autocorrelation and host anemone species drive variation in local components of fitness in a wild clownfish population - Marrot, Pascal; Fauvelot, Cécile; Berumen, Michael L; Srinivasan, Maya; Jones, Geoffrey P; Planes, Serge; Pujol, Benoit (Peer Community Journal)

(untitled)
The susceptibility of species to habitat changes depends on which ecological drivers shape individual fitness components. To date, only a few studies have quantified fitness components such as the Lifetime Reproductive Success across multiple generations in wild marine species. Because of a long-term sampling effort, such information is available for the population of wild orange clownfish, Amphiprion percula, from Kimbe Island (Papua New Guinea). Previous work on the wild orange clownfish near Kimbe Island suggests that there is little adaptive potential and that variation in LRS is mainly driven by a breeder’s habitat. Whether the host anemone species, geographic location, density or depth contributed to LRS remains however unknown because they were combined into a unique variable. We tested whether it is the ecology or the spatial distribution of clownfish that shaped the individual variation of a local fitness component, which would affect the population self-recruitment process and ultimately the maintenance of this wild population. Our spatially explicit analysis disentangled the role of these factors. We found that the host anemone species had an impact on wild clownfish LRS independently from their spatial distribution. The spatial distribution nevertheless had an impact on its own, as reflected by the spatial autocorrelation of LRS. Depth and density of anemones did not show a significant impact. Our findings imply that this clownfish population is susceptible to modifications of the spatial distribution and local assembly of anemone species